Cave-to-Mill: a Mine-to-Mill approach for block cave mines. (March 2015) - Nadolski, S.; Klein, B.; Elmo, D.; Scoble, M.
<x content-type="archive" xml:space="preserve">Abstract</x> A refinement of the traditional Mine-to-Mill integration opportunity for copper block cave mines is introduced here as a Cave-to-Mill production management concept. This is essentially the integration of underground mine production scheduling and monitoring with surface mineral processing management based upon fragment size and geometallurgical ore characteristics. Cave-to-Mill defines ore block models with respect to both mine and mill performance. Linkages between key cave and mill parameters have been established so that coordinated efforts towards maximizing net present value (NPV) can be made. Discrete fracture network (DFN) based methods were found to hold significant value within the Cave-to-Mill approach. The variable and relatively uncontrollable nature of cave fragmentation is considered to be a key distinguishing feature of Cave-to-Mill when compared with typical Mine-to-Mill strategies established for open-pit mines. It is envisioned that Cave-to-Mill will be an important design and operational strategy for block cave mines.